Risk factors for asthma exacerbations during pregnancy: a systematic review and meta-analysis - Annelies L. Robijn; Marleen P. Bokern; Megan E. Jensen; Daniel Barker; Katherine J. Baines; Vanessa E. Murphy (European Respiratory Review, 2022)
Background Conflicting literature exists regarding the risk factors for exacerbations among pregnant women with asthma. This systematic review and meta-analysis aimed to determine risk factors for asthma exacerbations during pregnancy. Methods Electronic databases were searched for the following terms: (asthma or wheeze) and (pregnan* or perinat* or obstet*) and (exacerb* or flare up or morbidit* or attack*). All studies published between 2000 and 24 August 2021 were considered for inclusion if they reported at least one potential risk factor of asthma exacerbations in pregnant women with asthma. Of the 3337 references considered, 35 publications involving 429 583 pregnant women with asthma were included. Meta-analyses were conducted to determine mean difference in risk factor between exacerbation groups, or the relative risks of exacerbation with certain risk factors. Good study quality was found through the Newcastle-Ottawa Scale (median score 8, interquartile range 7–9). Results Increased maternal age (mean difference 0.62, 95% CI 0.11–1.13), obesity (relative risk 1.25, 95% CI 1.15–1.37), smoking (relative risk 1.35, 95% CI 1.04–1.75), black ethnicity (relative risk 1.62, 95% CI 1.52–1.73), multiparity (relative risk 1.31, 95% CI 1.01–1.68), depression/anxiety (relative risk 1.42, 95% CI 1.27–1.59), moderate–severe asthma (relative risk 3.44, 95% CI 2.03–5.83, versus mild) and severe asthma (relative risk 2.70, 95% CI 1.85–3.95, versus mild–moderate) were associated with an increased risk of asthma exacerbations during pregnancy. Conclusions Future interventions aimed at reducing exacerbations in pregnancy could address the modifiable factors, such as smoking and depression/anxiety, and introduce more regular monitoring for those with nonmodifiable risk factors such as obesity and more severe asthma.